Performa berahi sapi PO pada berbagai BCS yang disinkronisasi dengan medroxy progesteron acetate di Satker Sumberejo Kendal - Muhammad Jamaluddin Ma'ruf; Edy Kurnianto; Sutiyono Sutiyono (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2017)
The objective of this study was to evaluate estrus appearance of Ongole Grade cattle on various Body Condition Score synchronized with medroxy progesterone asetat. Material used in this study was 68 head female Ongole Grade cattle and classified into 3 based on BCS, that was low (1-<4), midle (≥4-<7), high (≥7). Parameters of study was number of cattle showing estrus, appearance of vulva, mucus, uterus erection, speed and lenght of estrus. Collecting data was done since the synchronization was stopped and estrus detection was done at 8 am, 2 pm and 7 pm on 10 day. Data of this study was analized by descriptive mode and independent t-test. The result showed that cattle showing estrus in group of BCS 1-<4, ≥4-<7 and  ≥7 were 32%, 35% and 40%, respectively. The mode of color and temperature changing on BCS 1-<4, ≥4-<7 and ≥7 were + (100%); vulva swelling each group was + (100%), + (77,78%), + and – (50%), respectively, mode of mucus all of groups were + (100%), while uterus erection at each group of BCS were  +(100%), +(77,78%) and +(100%). Average of estrus speed on BCS 1-<4, ≥4-<7 and ≥7 were 364,6±117,65, 312,89±118,01 and 372±220,62, while estrus lenght BCS 1-<4, ≥4-<7 and ≥7 were 628,71±61,43, 533±190,19 and 422±121,62. In conclution, estrus synchronization did not give significant effect on various BCS. Various BCS showed that occurrence of estrus sign tended to same, but the middle BCS had better estrus length than that of small and high BCS.